2002
DOI: 10.1182/asheducation-2002.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Update on Epidemiology and Therapeutics for Non-Hodgkin’s Lymphoma

Abstract: This chapter presents updated information on the trends and patterns of non-Hodgkin's lymphoma (NHL) diagnoses as well as new information on chemotherapeutic and immunotherapeutic options for NHL treatment.In Section I, Dr. Brian Chiu summarizes the current knowledge regarding the etiologic factors and patterns of NHL as well as suggests future epidemiologic studies based on these preliminary results.In I. EPIDEMIOLOGY OF NON-HODGKIN'S LYMPHOMABrian C.-H. Chiu, PhD* Non-Hodgkin's lymphoma (NHL) is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 117 publications
(9 reference statements)
1
30
0
3
Order By: Relevance
“…In addition, conjugation of immunotherapeutic monoclonal antibodies with immunomodulators (such as α-Interferon) is also under clinical trials [145] . Other treatment approaches for NHL, drug regimen, efficacy and results of different clinical trials may be found elsewhere in more details [138,139,144,145] . In addition, novel therapeutic approaches, target pathways and potential small molecule inhibitors for treatment of NHL resistant to conventional treatment have also been reviewed recently [146] .…”
Section: Clinical and Therapeutics For Nhlmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, conjugation of immunotherapeutic monoclonal antibodies with immunomodulators (such as α-Interferon) is also under clinical trials [145] . Other treatment approaches for NHL, drug regimen, efficacy and results of different clinical trials may be found elsewhere in more details [138,139,144,145] . In addition, novel therapeutic approaches, target pathways and potential small molecule inhibitors for treatment of NHL resistant to conventional treatment have also been reviewed recently [146] .…”
Section: Clinical and Therapeutics For Nhlmentioning
confidence: 99%
“…This therapy is among the best treatment for NHL, as NHL is highly radiosensitive. In this therapy, Iodine-131 (Tositumomab) or the Yttrium-90 (Ibritumomab tiuxetan) is conjugated to antibodies against CD20, increasing the specificity, while diminishing off-target damage [145] . In addition, conjugation of immunotherapeutic monoclonal antibodies with immunomodulators (such as α-Interferon) is also under clinical trials [145] .…”
Section: Clinical and Therapeutics For Nhlmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-Hodgkin's lymphoma (NHL) is the sixth leading cause of cancer death in the United States and has increased in incidence by >80% since 1973 (1,2). NHL can be divided into at least 29 different subtypes of malignancy of either T-or Blymphocyte origin.…”
mentioning
confidence: 99%